2007
DOI: 10.1007/s00192-006-0287-3
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal reconstruction with sigmoid colon in vaginal agenesis

Abstract: This study was conducted to evaluate the anatomical and functional results of sigmoid colon vaginoplasty. From June 2000 to June 2005, 26 patients with congenital vaginal agenesis were evaluated and treated with sigmoid colon reconstruction at Ain Shams University Maternity Hospital as a primary procedure in 17 patients and a secondary procedure in 9 patients after previous failed Abbe-McIndoe vaginoplasty elsewhere. The anatomical results were good in 22 patients, while 3 patients suffered from introital sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…One case without sexual life experience did not report discomforts of irritation or difficult usage of mold vagina. The sexual life satisfaction rate in this study is similar to the reported level of more than 80% [22,23], which further confirmed the orthopedic effect of sigmoid vaginoplasty. It has been reported that the neovagina was relatively insensitive and may have excess mucus production requiring the patient to wear pads permanently [3].…”
Section: Discussionsupporting
confidence: 93%
“…One case without sexual life experience did not report discomforts of irritation or difficult usage of mold vagina. The sexual life satisfaction rate in this study is similar to the reported level of more than 80% [22,23], which further confirmed the orthopedic effect of sigmoid vaginoplasty. It has been reported that the neovagina was relatively insensitive and may have excess mucus production requiring the patient to wear pads permanently [3].…”
Section: Discussionsupporting
confidence: 93%
“…[14][15][16][17] and that of laparoscopy group was 8.5 days (IQR, [7][8][9][10][11]. No patients developed intestinal obstruction, bowel adhesions, intestinal perforation, contracture of the mucocutaneous junction, ulcerative colitis, or fistula.…”
Section: Resultsmentioning
confidence: 99%
“…Vaginoplasty using rectosigmoid colon allows a reduced rate of vaginal contracture and shortening. It also has excellent advantages in the sufficient gain in vaginal length, natural mucous secretion with a normal lubricating effect, which is credited as the most natural way of mimicking the normal vagina that can be obtained by the use of extravaginal tissue [2][3][4][8][9][10][11]. However, it also accompanies incision of the intraperitoneal cavity after perineal dissection and incision into the abdominal wall to procure the segment of rectosigmoid colon, which may be associated with postoperative adhesive complications of the bowel.…”
Section: Introductionmentioning
confidence: 99%
“…The American College of Obstetrics and Gynaecology suggests progressive dilatation as the first-line treatment for vaginal agenesis, and surgery is offered to those patients who failed the conservative techniques [7]. Surgical procedure options include use of bowel segments, peritoneum (Davydov's technique), Vecchietti's operation and Abbé-McIndoe vaginoplasty [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%